The Electric Field Induced Strain-Electrostrictive Response-of Polyurethane Elastomers - KOJIMA, Kenzo; ASAI, Kiyotsugu; INOUE, Shin-ichi; OKAMOTO, Hiroshi (KOBUNSHI RONBUNSHU, 1999)
The electric field induced strain-electrostrictive response-of polyurethane elastomers (PUEs) was experimentally investigated. The electrostriction measuring method without experimental errors from the flexure motion and the mechanical constrains for flexible samples, such as a rubber whose modulus is from 106Pa to 107Pa, was established using 400Pa-loaded samples and completely constrained samples, and the electrostriction coefficients of the samples were compared. The influence of microphase separation on the electrostriction coefficients was investigated in PUEs prepared from poly (ether glycol) s, such as polyoxytetramethylene glycol, polyoxypropylene glycol, and polyoxy-1, 2-butylene glycol, 1, 4-butanediol (1, 4-BD), trimethylolpropane (TMP), and 4, 4'-diphenylmethane diisocyanate (MDI). The molar ratio of a poly (ether glycol), 1, 4-BD, TMP, and MDI was 1: 0.8: 0.13: 2. PUEs with hard segment aggregates of poor order were obtained at a high curing temperature (180°C). PUEs cured at 180°C had much larger electrostriction coefficients than those cured at 100°C. The results showed that making order of hard segment aggregates poorer is a very useful way for the improvement of electrostrictive effect in PUE with the same composition.